Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.5194/acp-18-17637-2018
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive organic emission profiles for gasoline, diesel, and gas-turbine engines including intermediate and semi-volatile organic compound emissions

Abstract: Abstract. Emissions from mobile sources are important contributors to both primary and secondary organic aerosols (POA and SOA) in urban environments. We compiled recently published data to create comprehensive model-ready organic emission profiles for on- and off-road gasoline, gas-turbine, and diesel engines. The profiles span the entire volatility range, including volatile organic compounds (VOCs, effective saturation concentration C*=107–1011 µg m−3), intermediate-volatile organic compounds (IVOCs, C*=103–… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
139
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(154 citation statements)
references
References 68 publications
(149 reference statements)
14
139
0
1
Order By: Relevance
“…Previously it has been shown that IVOCs alone create about 50% of the formed 30 SOA from the gasoline vehicle exhaust (Zhao et al, 2016). The same observation was previously reported in a more recent publication, where comprehensive organic emission profiles for relatively new gasoline vehicles were constructed based on previous studies (Lu et al, 2018). The conclusion of that study was that IVOCs and SVOCs contribute approximately 50% to Atmos.…”
Section: Photochemistry Of Gdisupporting
confidence: 72%
See 2 more Smart Citations
“…Previously it has been shown that IVOCs alone create about 50% of the formed 30 SOA from the gasoline vehicle exhaust (Zhao et al, 2016). The same observation was previously reported in a more recent publication, where comprehensive organic emission profiles for relatively new gasoline vehicles were constructed based on previous studies (Lu et al, 2018). The conclusion of that study was that IVOCs and SVOCs contribute approximately 50% to Atmos.…”
Section: Photochemistry Of Gdisupporting
confidence: 72%
“…CC BY 4.0 License. the formed SOA from gasoline vehicle exhaust, even if VOCs clearly dominate the emission profile (Lu et al, 2018). Based on the results of these previous studies, we can assume that also in our study GDI vehicle emitted IVOCs and SVOCs, and these emissions made a substantial contribution to formed SOA.…”
Section: Photochemistry Of Gdisupporting
confidence: 68%
See 1 more Smart Citation
“…Organic aerosol (OA), including SOA, is detrimental to human health, but in addition to that, OA, and particularly SOA, affects air quality and climate by contributing to the formation of visibilityreducing haze and influencing the size distribution, chemical composition, and radiative and cloud formation properties of the atmospheric particles (Kanakidou et al, 2005;Hallquist et al, 2009). As the vehicular emission standards have become stricter, the absolute emissions of the regulated pollutants, such as VOCs, carbon monoxide, NO x , and PM, have substantially decreased, leading to decreases in SOA and O 3 formation as well May et al, 2014;Gentner et al, 2017;Saliba et al, 2017;. However, despite the emission reductions, the newest generation of gasoline vehicles still emits substantial amounts of volatile organic and inorganic compounds, including sulfur dioxide (SO 2 ) and NO x , and once released from the tailpipe, they react with the atmospheric oxidants, resulting in the formation of secondary air pollutants, such as SOA and O 3 Karjalainen et al, 2016;Zhao et al, 2017Zhao et al, , 2018Saliba et al, 2017).…”
mentioning
confidence: 99%
“…Moreover, driving conditions significantly affect the emissions and formed amount of SOA. For example cold-start and idling emissions are significantly higher, leading to greater SOA formation compared to hot-start or stable driving conditions with a heated engine (Weilenmann et al, 2009;Schifter et al, 2010;Nordin et al, 2013;May et al, 2014;Saliba et al, 2017).…”
mentioning
confidence: 99%